2009
DOI: 10.1016/j.fitote.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic and chlorogenic acids in Ilex paraguariensis extracts are the main inhibitors of AGE generation by methylglyoxal in model proteins

Abstract: The present study concentrates on the evaluation of the anti-glycation effect of some bioactive substances present in yerba maté (Ilex paraguariensis): 5-caffeoylquinic acid, caffeic acid and a sapogenin (oleanolic acid). Bovine serum albumin and histones were incubated in the presence of methylglyoxal with or without the addition of 5-caffeoylquinic acid, caffeic acid and oleanolic acid. After the incubation period, advanced glycation end product (AGE) fluorescence spectra were performed and protein structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(100 citation statements)
references
References 30 publications
3
93
0
4
Order By: Relevance
“…In addition polyphenols such as caffeoylquinic, p-coumaroylquinic, feruloylquinic and dicaffeoylquinic acids contributed to about 70% of the antioxidant capacity of the coffee fractions [51]. Notably, Ilex paraguariensis, like coffee, contains a high concentration of caffeic acid, mostly esterified as chlorogenic acids [65]. Large amounts of chlorogenic acid were identified also in Chrysanthemum morifolium R. [42].…”
Section: Cinnamic Acids and Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition polyphenols such as caffeoylquinic, p-coumaroylquinic, feruloylquinic and dicaffeoylquinic acids contributed to about 70% of the antioxidant capacity of the coffee fractions [51]. Notably, Ilex paraguariensis, like coffee, contains a high concentration of caffeic acid, mostly esterified as chlorogenic acids [65]. Large amounts of chlorogenic acid were identified also in Chrysanthemum morifolium R. [42].…”
Section: Cinnamic Acids and Derivativesmentioning
confidence: 99%
“…Several studies have demonstrated that the anti-glycation activity correlates significantly with the phenolic content of the tested plant extracts [5,50,59,64,65]. Polyphenols are the most abundant dietary antioxidants, being common constituents of fruits, vegetables, cereals, seeds, nuts, chocolate, and beverages, such as coffee, tea, and wine.…”
Section: Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeic and chlorogenic acids, predominant phytochemicals of I. paraguariensis extract, have shown more powerful antiglycation properties than aminoguanidine. They interfere glucose metabolism by free radicals scavenging or chelating of transition metal ions [85].…”
Section: Free Radical Scavengingmentioning
confidence: 99%
“…Wu et al reported that guava extract inhibited Amadori product formation in a dose dependent manner through chelating activity mechanism [89]. Chlorogenic acids, found in edible parts of some plants such as apple, strawberries, pineapple, blueberries, coffee and sunflower act as anti-AGEs by metal chelating, or modulation of antioxidant enzymes gene expression [85]. Rutin as an antioxidant also possesses a chelating property and decreases the Fenton reaction as a source of free radical formation.…”
Section: Metal Chelating Activitymentioning
confidence: 99%